Endodontic regenerative treatment for internal radicular resorption using bio-ceramic material, case report - Duque-Urióstegui, Cristhal; Duque-Urióstegui, Carla B.; Barrera-Mera, Baltazar; Díaz-Bárcenas, Rebeca J.; Alavez-García, Tonatiuh; Vega-Arenas, Lucía; Bolaños-Lezama, Karla A.; López, Andrea Anaya; Alarcón-Méndez, Sandra J.; Castañeda-Palacios, Gabriela; Cruz-Zúñiga, Miguel A.; Muñoz-Ramírez, Yanirethe I.; et al. (International Journal of Research in Medical Sciences, 2021)
The internal resorption of the internal radicular conduct is a process than can be both physiological or pathological, being the osteoclasts, odontoclasts and dentinoclast responsible for said process. 49-year-old female patient, refers orthodontic treatment at age 20, attends a dental check-up due to pain when chewing. Dental organ (DO) #11 was diagnosed with internal root resorption and symptomatic, suppurative apical periodontitis. Treatment started performing an endodontic access and taking a conductometry reading with an apical foramen locator, using a precision hybrid instrumentation technique and applying hypochlorite irrigation, the intra-canal was medicated with chemically pure calcium hydroxide for 7 days. The canal obturation was repaired infiltrating a bio-ceramic material (BIO-C Sealer) followed by the placement of the single cone using a vertical condensation technique.